Impact of Decision 399 by CAN for Governance in the Municipality of Tulcan, Ecuador - Cevallos Suárez, Marco Polo (2022)
The Andean Community (CAN) adopted, back in 2012, an assembly of regulations to facilitate commercial transport at the under-regional level as well as the integration of its territories. One of these regulations is Decision 399, regarding international transport of merchandise via ground roads. The objective of this research was to analyze the situational status of merchandise flow, heavy cargo transport and the social-economic impact of Decision 399 on the governance of the municipality of Tulcan. The methodology involved was non-experimental, cross-sectional, descriptive, and the technique involved was the survey, as well as a randomized non-probabilistic sample. The study showed that 2457 people were unemployed and 9 818 had their income affected upon implementation of this Decision on the heavy transport sector, as well as others also associated to this economic activity.